POLA ASUH ORANG TUA TERHADAP ANAK USIA DINI DI ERA DIGITAL(Studi Kasus Di TK PGRI Winaya Mekar Ciracap) - Yani Nuraeni; Indra Zultiar; Asep Munajat (CV. ADIBA AISHA AMIRA, 2024)
This journal is motivated by the rise of electronic devices in children's daily lives which has changed their lives. As they raise their children in the digital age, parents should focus on helping them develop positive self-perception and response skills so they can make good use of digital gadgets. Knowing how the PGRI Winaya Mekar Kindergarten in Cikangkung Village, Ciracap District responds to the impact of digital technology on early childhood education is the aim of this research. Case study research is the method of choice in this qualitative investigation. Triangulation, a combinational data collection method, emphasizes meaning rather than generalization in analysis. Meanwhile, the Miles & Huberman interactive model is used for data analysis, namely data reduction, data presentation, and drawing conclusions. The findings of this study include (1) the application of a democratic and permissive parenting style by parents in raising children in the modern digital era. One approach to raising children is known as “permissive parenting”, which advocates letting children know who they are. Democratic parenting style: This approach to raising children usually gives parents greater freedom, but this approach also sets ground rules based on references that have been agreed upon by parents and children. The first negative impact of parenting patterns that are too permissive on children's development in the modern digital era is that many children are very independent, have difficulty adjusting to their peers, and are often disobedient. Second, one of the advantages of democratic parenting is that it encourages children to speak up and share ideas. When parents set limits based on their children's abilities, it helps them express themselves and develop creativity, innovation and a sense of responsibility.